Effect of imagery on passion for physical activity in individuals with type 2 diabetes / Anaurene Roy - Anaurene, Roy (2018)
Passion is a motivational force towards an activity that is internalised into a person’s identity when the individual enjoys the activity. Passion has two types: harmonious passion (HP) and obsessive passion (OP). Imagery is a widely applied technique for developing psychological variables, such as passion, in sport and physical activity (PA) contexts. I examined the effects of imagery on passion and the impact of changes in passion on preferred PA for people with Type 2 diabetes mellitus (T2DM). In Study 1, I developed the Physical Activity Imagery Questionnaire (PAIQ), which comprised of 15-items on two subscales, showing sound validity and reliability. In Study 2, I examined the relationship between types of imagery use and types of passion in people with T2DM to determine the most effective type of imagery to develop passion for PA. I measured types of imagery use using the PAIQ and types of passion with the Passion Scale (PS). I found that there were significant relationships of cognitive imagery use and motivational imagery use with HP with smaller correlations with OP. Multiple Regression results showed that cognitive and motivational imagery use significantly predicted HP. The results indicated that both types of imagery use could increase HP when presented in an imagery intervention. In Study 3, I examined the effect of a harmonious passion imagery (HPI) intervention and a general physical activity imagery (GPAI) intervention on passion for PA in 20 voluntary male and female participants with T2DM, aged between 32 and 65 years. Participants in both conditions practised imagery for two face-to-face, individual sessions per week for six weeks and then two self-managed imagery sessions for a further six weeks. Ten participants, assigned at random, practised the HPI intervention, including cognitive and motivational imagery related to HP. Cognitive imagery included images of the place where each individual normally exercised. It also included images of the individual warming up, exerting more effort and cooling down. Motivational imagery included images of enjoying the activity, goal accomplishment, and positive experience associated with completion of the task. The other 10 participants practised a GPAI intervention with no passion-related content. The script included images of the individual performing and completing their respective activity. Using a two-way, mixed-design ANOVA, I found a significant difference, p < .05, between the HPI and GPAI conditions with a greater increase in HP for Weeks 0 to 6 for the HPI condition. I also found a significant difference, p < .05, between the HPI and GPAI conditions with a greater increase in PA for Weeks 0 to 12 for the HPI condition. There was no significant difference in OP in HPI and GPAI conditions. These results supported the proposition that an imagery intervention focused on HP was an effective cognitive-behavioural technique that led to an increase in HP for a preferred PA, as well as increased PA. In Study 4, I explored the subjective experience of participants, from the HPI condition, who showed an increase in HP for preferred PA. Two themes identified were lifestyle involvement in PA before and after the onset of T2DM and passion imagery as a pathway to HP development. This research indicates that an imagery intervention focused on HP is an effective, non-invasive, cognitive-behavioural technique that enhanced HP for a preferred PA and increased amount of participation in PA.